Primary squamous cell carcinoma of the sigmoid colon - Sahu, Subrata Kumar; Mishra, Ipseet; Haldar, Sudip; Bhattacharryya, Samir (Indian Journal of Case Reports, 2019)
Primary squamous cell carcinoma (SCC) of the colon and rectum is a rare malignancy. Overall there are less than 150 cases which have been reported and the first was case was reported in 1919. We report a case of pure SCC involving the sigmoid colon. A 55 year old woman presented with chief complaints of bleeding per rectum for 5 months, anorexia and abdominal pain. Histological diagnosis of SCC was made by colonoscopy biopsy. Later it was confirmed by immunohistochemistry (IHC). Any other possible primary sites of malignancy were excluded. Complete surgical resection was performed. The prognosis of this disease seems to be worse than that of adenocarcinoma.